The Numerical Solutions of FIEs of the Second Kind of Degenerated Type Using Bownd's Methods - Saleh, Atefa J. (Journal of Informatics and Mathematical Sciences, 2021)
In this work, we consider the numerical solutions of some types of Fredholm integro-differential equations (FIDEs). Namely, Bownd's, successive, Adomian's and the improved methods are used to solve linear Fredholm integro-differential equations (FIDEs). In addition, some numerical examples are given to show the efficiency and accuracy of the proposed methods. The numerical results show that using the improved methods is the best technique to solve such types of problems.